2021
DOI: 10.3329/birdem.v12i1.57220
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological patterns in patient with Guillain-Barre syndrome

Abstract: Background: Guillain-Barre syndrome (GBS) is an acute, frequently severe and fulminant polyradiculoneuropathy that is autoimmune in nature. Incidence and predominant subtypes of GBS differ geographically. Electrophysiology has important role in subtyping GBS. This study aimed to evaluate the electrophysiological findings in patient of GBS. Methods: This was a hospital based cross-sectional descriptive study and conducted at the Department of Neurology in Sir Salimullah Medical College & Mitford Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The predominant subtype was acute inflammatory demyelinating polyneuropathy (48.0%) 23 . Another study showed that, demyelinating neuropathy was more common that axonal variety 26 . There was significant statistical difference between AIDP, AMAN and AMSAN groups of patients if we consider GBS disability score and MRC score at entry and at nadir.…”
Section: Lab Parameters Cell Countmentioning
confidence: 96%
“…The predominant subtype was acute inflammatory demyelinating polyneuropathy (48.0%) 23 . Another study showed that, demyelinating neuropathy was more common that axonal variety 26 . There was significant statistical difference between AIDP, AMAN and AMSAN groups of patients if we consider GBS disability score and MRC score at entry and at nadir.…”
Section: Lab Parameters Cell Countmentioning
confidence: 96%